Psychological well-being in students during self-isolation due to the COVID-19 pandemic - Spasovski, Ognen; Kenig, Nikolina (Primenjena psihologija)
The COVID-19 pandemic resulted in lock-down measures being imposed by the government of North Macedonia. Conditions of self-isolation have direct effects on mental health. We researched the possible protective factors of psychological well-being. A total of 510 college students from the biggest university in the country (70% females, Mage = 21.12 years, SD = 1.58) responded to a structured online questionnaire, one month after the country's lock down. Multiple linear regression analysis was performed on hypothesized protective factors of well-being. Results showed that significant predictors of the psychological well-being in conditions of isolation are: perceived social support during self-isolation, self-engagement in physical exercises, perception of being adequately informed about the virus and the ways of protection, and the tendency to hold conspiracy explanations about the virus and pandemic. Perception of medical and restriction of movement measures, together with self-engagement in reading /watching movies, were not significant predictors. In the face of the expected further difficulties with the pandemic, policy creators and the scientific community should develop well-thought out strategies, tailored to different groups, in order to provide appropriate support to people to cope with pandemic, to adequately communicate the necessary medical and restriction measures and all important information about the virus and pandemic, especially in order to manage with the complex role of the conspiracy theories which could undermine confidence in the health system.